COVID-19 and dental sleep medicine: Risks, precautions and patient guidance - Cunha, Thays Crosara Abrahaõ; Rossi, Rowdley; Marson, Lilian Chrystiane Giannasi [UNESP]; Guimaraes, Thais M; MacHado, Marco Antônio Cardoso; Meira-E-Cruz, Miguel; Ferraz, Otávio; Filho, Milton Maluly; Cunali, Paulo Afonso; Júnior, Cauby Maia Chaves; Dal-Fabbro, Cibele (My University, 2020)
COVID-19 is the offcial name for the disease caused by SARS-CoV-2, which has become a pandemic, infecting more than 5 million people worldwide. Transmission occurs by inhaling droplets generated when an infected person coughs, sneezes or exhales, or by touching contaminated surfaces and then rubbing their hands over their eyes, nose or mouth. Some infected people become seriously ill, while others have no symptoms, but even though they are asymptomatic, they can still transmit the virus. As vaccines and effective medications do not yet exist, the only way to handle the devastating consequences of the pandemic is prevention. Quality of sleep is essential for the immune system to be prepared to receive, fight and restore itself after a viral infection. Therefore, patients with obstructive sleep apnea (OSA) should continue treatment, and only suspend or change the therapeutic modality under the guidance of a sleep physician. In the era of COVID-19, due to the high probability of contamination promoted by CPAP, the mandibular repositioning device has been considered as the first choice for patients with OSA. However, as the dental approach is at high risk of contamination, due to the proximity of the dental surgeon to the patient, it is essential that the professional who works in this field knows the risks to which they are exposed. Precautions must be adopted and patients should be guided in order to control and use of their intraoral devices.
Keywords: Coronavirus infections; Dentistry; Obstructive; Sleep; Sleep apnea